Difference between revisions of "009B Sample Midterm 1, Problem 1"
Jump to navigation
Jump to search
Line 1: | Line 1: | ||
<span class="exam">Evaluate the indefinite and definite integrals. | <span class="exam">Evaluate the indefinite and definite integrals. | ||
− | + | <span class="exam">(a) <math>\int x^2\sqrt{1+x^3}~dx</math> | |
− | + | ||
+ | <span class="exam">(b) <math>\int _{\frac{\pi}{4}}^{\frac{\pi}{2}} \frac{\cos(x)}{\sin^2(x)}~dx</math> | ||
Line 8: | Line 9: | ||
!Foundations: | !Foundations: | ||
|- | |- | ||
− | | How would you integrate <math style="vertical-align: -12px">\int \frac{\ln x}{x}~dx?</math> | + | | How would you integrate <math style="vertical-align: -12px">\int \frac{\ln x}{x}~dx?</math> |
+ | |- | ||
+ | | | ||
+ | You can use <math style="vertical-align: 0px">u</math>-substitution. | ||
+ | |- | ||
+ | | Let <math style="vertical-align: -5px">u=\ln(x).</math> | ||
+ | |- | ||
+ | | Then, <math style="vertical-align: -13px">du=\frac{1}{x}dx.</math> | ||
|- | |- | ||
| | | | ||
− | + | Thus, | |
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
\displaystyle{\int \frac{\ln x}{x}~dx} & = & \displaystyle{\int u~du}\\ | \displaystyle{\int \frac{\ln x}{x}~dx} & = & \displaystyle{\int u~du}\\ | ||
&&\\ | &&\\ | ||
& = & \displaystyle{\frac{u^2}{2}+C}\\ | & = & \displaystyle{\frac{u^2}{2}+C}\\ | ||
&&\\ | &&\\ | ||
− | & = & \displaystyle{\frac{(\ln x)^2}{2}+C.} | + | & = & \displaystyle{\frac{(\ln x)^2}{2}+C.} |
\end{array}</math> | \end{array}</math> | ||
|} | |} | ||
+ | |||
+ | |||
'''Solution:''' | '''Solution:''' | ||
Line 28: | Line 38: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |We | + | |We use <math style="vertical-align: 0px">u</math>-substitution. |
|- | |- | ||
− | | | + | |Let <math style="vertical-align: -2px">u=1+x^3.</math> |
|- | |- | ||
− | | | + | |Then, <math style="vertical-align: 0px">du=3x^2dx</math> and <math style="vertical-align: -13px">\frac{du}{3}=x^2dx.</math> |
− | ::<math style="vertical-align: -13px">\frac{1}{3}\int \sqrt{u}~du.</math> | + | |- |
+ | |Therefore, the integral becomes | ||
+ | |- | ||
+ | | <math style="vertical-align: -13px">\frac{1}{3}\int \sqrt{u}~du.</math> | ||
|} | |} | ||
Line 39: | Line 52: | ||
!Step 2: | !Step 2: | ||
|- | |- | ||
− | |We now have | + | |We now have |
|- | |- | ||
− | | | + | | <math>\begin{array}{rcl} |
− | + | \displaystyle{\int x^2\sqrt{1+x^3}~dx} & = & \displaystyle{\frac{1}{3}\int \sqrt{u}~du}\\ | |
− | \displaystyle{\int x^2\sqrt{1+x^3}~dx} | ||
− | |||
− | & = & \displaystyle{\frac{1}{3}\int \sqrt{u}~du}\\ | ||
&&\\ | &&\\ | ||
& = & \displaystyle{\frac{2}{9}u^{\frac{3}{2}}+C}\\ | & = & \displaystyle{\frac{2}{9}u^{\frac{3}{2}}+C}\\ | ||
&&\\ | &&\\ | ||
− | & = & \displaystyle{\frac{2}{9}(1+x^3)^{\frac{3}{2}}+C.} | + | & = & \displaystyle{\frac{2}{9}(1+x^3)^{\frac{3}{2}}+C.} |
\end{array}</math> | \end{array}</math> | ||
|} | |} | ||
Line 57: | Line 67: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | | | + | |We use <math>u</math>-substitution. |
|- | |- | ||
− | |Plugging in our values into the equation <math style="vertical-align: -5px">u=\sin(x),</math> we get <math style="vertical-align: -15px">u_1=\sin\bigg(\frac{\pi}{4}\bigg)=\frac{\sqrt{2}}{2}</math> and <math style="vertical-align: -16px">u_2=\sin\bigg(\frac{\pi}{2}\bigg)=1.</math> | + | |Let <math style="vertical-align: -5px">u=\sin(x).</math> |
+ | |- | ||
+ | |Then, <math style="vertical-align: -5px">du=\cos(x)dx.</math> | ||
+ | |- | ||
+ | |Also, we need to change the bounds of integration. | ||
+ | |- | ||
+ | |Plugging in our values into the equation <math style="vertical-align: -5px">u=\sin(x),</math> we get | ||
+ | |- | ||
+ | | <math style="vertical-align: -15px">u_1=\sin\bigg(\frac{\pi}{4}\bigg)=\frac{\sqrt{2}}{2}</math> and <math style="vertical-align: -16px">u_2=\sin\bigg(\frac{\pi}{2}\bigg)=1.</math> | ||
|- | |- | ||
|Therefore, the integral becomes | |Therefore, the integral becomes | ||
|- | |- | ||
− | | | + | | <math style="vertical-align: -19px">\int_{\frac{\sqrt{2}}{2}}^1 \frac{1}{u^2}~du.</math> |
− | |||
|} | |} | ||
Line 70: | Line 87: | ||
!Step 2: | !Step 2: | ||
|- | |- | ||
− | |We now have | + | |We now have |
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
\displaystyle{\int _{\frac{\pi}{4}}^{\frac{\pi}{2}} \frac{\cos(x)}{\sin^2(x)}~dx} & = & \displaystyle{\int_{\frac{\sqrt{2}}{2}}^1 \frac{1}{u^2}~du}\\ | \displaystyle{\int _{\frac{\pi}{4}}^{\frac{\pi}{2}} \frac{\cos(x)}{\sin^2(x)}~dx} & = & \displaystyle{\int_{\frac{\sqrt{2}}{2}}^1 \frac{1}{u^2}~du}\\ | ||
&&\\ | &&\\ | ||
Line 80: | Line 97: | ||
& = & \displaystyle{-\frac{1}{1}-\frac{-1}{\frac{\sqrt{2}}{2}}}\\ | & = & \displaystyle{-\frac{1}{1}-\frac{-1}{\frac{\sqrt{2}}{2}}}\\ | ||
&&\\ | &&\\ | ||
− | & = & \displaystyle{-1+\sqrt{2}.} | + | & = & \displaystyle{-1+\sqrt{2}.} |
\end{array}</math> | \end{array}</math> | ||
|} | |} | ||
+ | |||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
!Final Answer: | !Final Answer: | ||
|- | |- | ||
− | | '''(a)''' <math>\frac{2}{9}(1+x^3)^{\frac{3}{2}}+C</math> | + | | '''(a)''' <math>\frac{2}{9}(1+x^3)^{\frac{3}{2}}+C</math> |
|- | |- | ||
− | | '''(b)''' <math>-1+\sqrt{2}</math> | + | | '''(b)''' <math>-1+\sqrt{2}</math> |
|} | |} | ||
[[009B_Sample_Midterm_1|'''<u>Return to Sample Exam</u>''']] | [[009B_Sample_Midterm_1|'''<u>Return to Sample Exam</u>''']] |
Revision as of 10:59, 9 April 2017
Evaluate the indefinite and definite integrals.
(a)
(b)
Foundations: |
---|
How would you integrate |
You can use -substitution. |
Let |
Then, |
Thus, |
|
Solution:
(a)
Step 1: |
---|
We use -substitution. |
Let |
Then, and |
Therefore, the integral becomes |
Step 2: |
---|
We now have |
(b)
Step 1: |
---|
We use -substitution. |
Let |
Then, |
Also, we need to change the bounds of integration. |
Plugging in our values into the equation we get |
and |
Therefore, the integral becomes |
Step 2: |
---|
We now have |
|
Final Answer: |
---|
(a) |
(b) |